Characteristics of chemical reaction and convective boundary conditions in Powell-Eyring nanofluid flow along a radiative Riga plate. Issue 4 (April 2019) - Rasool, Ghulam; Zhang, Ting
Abstract: A typical base fluid such as water, oil or glycol is poor conductor of heat due to deficient thermo-physical properties. This deficiency is normally addressed by saturation of thermally strong conductive metallic nanoparticles such as Fe, Ti, Hg, Cu, Au into the base fluid resulting a stronger thermal conductivity, electric conductivity, heat and mass flux of the so formulated nanofluid. Nanoparticles having a diameter size less than 100 nano-meter are preferred in this formulation because these nano-sized particles stay suspended into the base fluid for a longer time-period. This communication aims to investigate the salient features of a nanofluid flow along a radiative Riga plate using Powell-Eyring model and convective boundary conditions. The flow model involves the effect of first order chemical reaction as well as the Brownian motion diffusion and Thermophoresis effects. Governing PDEs are transformed into ODEs using suitable transformations. HAM is applied for convergent series solutions to the boundary value problem. Impact of various parameters including Brownian motion, Thermophoresis, modified Hartman number, Lewis and Prandtl number on flow profiles is analyzed graphically. Parameters of physical interest like Skin-friction, Nusselt and Sherwood numbers are illustrated through numerical data. Effect of modified Hartman number is significant on flow profiles due to involvement of Riga plate. An efficiency is achieved in fluid flow and heat-mass flux through suspension of nanoparticles in base fluid.